The utilization of calcium carbonate as growth promoter in lactate fermentation - Sadi, bin Sujang. (Universiti Malaysia Sarawak (UNIMAS), 2004)
A homofermentative bacterium, Lactococcus laclis 10-1, produces purely L-Iactate on glucose. Iu pTesent studies, Calcium Carbonate (CaCO,) was utilized as a growth promoter in order to enhance lactate productivity, Addition various concentration (w/v) of Caco, to culture at the 8 h of fennentation process had a positive effects on both biomass and lactate production. After 24 hrs, pH of the fennentation culture was between 5.0 -6.0 and the highest lactate production was 32.08 giL with the glucose consumption of 25.49 giL .